The importance of ultrasonography examination in renal abscesses in pediatric patients - Kowalczyk, Katarzyna; Ożóg, Katarzyna; Klęba, Joanna; Kucharska-Miąsik, Iwona; Guzik, Anna; Guz, Wiesław (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Renal abscess is a rare finding in the pediatric population, estimated at 0.2% of all intra-abdominal abscesses. The most common manifestations are fever, flank pain and simultaneously increased inflammatory markers in laboratory tests. Symptoms of this condition are non-specific and can be dismissed with other pathologies like renal tumor. Although the management is based on widespread antibiotic therapy, some cases need surgical intervention because of poor general condition and major diameter of abscess (>5 cm). We undertook this study to analyze the ultrasonography findings correlated with the clinical manifestations of renal abscesses in children that can potentially improve detecting renal abscesses in children earlier. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. We retrospectively studied 9 patients with renal abscesses treated in our hospital. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. All patients were diagnosed with renal abscesses based on ultrasonography (US) examination and each of them had elevated inflammatory parameters at the time of admission. For treatment, all patients were treated with intravenous antibiotics and two of them were treated with surgical drainage. All study group recovered completely or received a reduction of abscesses diameters. The renal abscesses were monitored by ultrasonography. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. In our study, we assessed the usefulness of the US examination for diagnosis and treatment monitoring in pediatric patients. Ultrasonography is a gold standard due to its wide availability, noninvasiveness and low price. It also allows for immediate diagnosis, which is crucial to institute proper treatment. Treatment of abscesses depends on the clinical condition of the patient, other comorbidities, imaging presentation and the size of the abscess.